PERTUMBUHAN DAN DAYA HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) DENGAN APLIKASI PUPUK GUANO DAN NPK - M. Fahim Amin; Armaini Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research aims to determine the effect Guano dan NPK fertilizer for the get interaction aplication Guano and NPK fertilizer for the growth and productthe results shallot (Allium ascalonicum L.). This research was aplied at agriculture experiment station of agricultural faculty Riau University, Pekanbaru City. This research start from January and finish at March 2019. This is are experiment researh by using Randomized Group Design (RGD) consisting of two factor. The first factor is aplication guano fertilizer for the three doses is G1 (500 g per plot), G2 (1000 g per plot), G3 (1500 g per plot). The two factor is aplication NPK fertilizer to three doses is N1 (10 g per plot), N2 (20 g per plot), N3 (30 g per plot). Combination two factor this is are mine treatment and every combination treatment replication for the three at twenty seven unit experiment. The results of this research showed combination aplication Guano 10 ton.ha-1 and NPK fertilizer 200 kg.ha-1 are the best doses for the can increases growth and products shallot (Allium ascalonicum L.) for the every parameters. Keywords : Allium ascalonicum L., Guano fertilizer, NPK fertilizer.